Stakeholders’ Roles in Implementing Public-Private Partnerships in the State of Bahia, Brazil - Cabral, Sandro (2016)
This article analyzes stakeholders’ roles in implementing Public-Private Partnerships (PPPs) in the state of Bahia, Brazil. The research encompassed three experiences in the fields of health, sanitation, and sport/culture and it assessed all stages in the life cycle of each PPP, from the early stage of matching the proposal to contract execution, going through the funding and construction stages. The main findings show that the various stakeholder types (deliberative, claimant, controller, and funder) have converging and diverging stake patterns over the PPPs life cycle. In the same vein, survey findings reveal that the various stakeholders seem to be less prepared for the later project stages. Such results contribute to the current debates on applying the stakeholder theory to the public sector domain by providing a prospective view of the working patterns of various stakeholder groups in innovative organizational arrangements such as the PPPs.